Prevalence of migraine in patients with fibromyalgia - Vieira, Lucas Dias Miguel Moreira (2023)
ObjectiveTo evaluate the prevalence of migraine in patients with fibromyalgia and the impacts of these comorbidities on the daily life of patients.MethodsQuestionnaires were applied to fibromyalgia patients. The questionnaires were applied through a Google forms application link and in person, printed. We used FIQ, PHQ-9, and ID migraine. And for patients with a positive ID migraine, we applied the Midas subsequently.ResultsSeventy fibromyalgia patients were recruited, age of 47.31 ± 14.5 years. Sixty-five (92.86%) were female and 5 (7.14%) were male. We obtained a prevalence of 60% (n = 42) of migraine associated with fibromyalgia. Among the analyzed variables, severity of depression (p = 0.007), aggregate severity of depression (p = 0.004), and impact of fibromyalgia (p = 0.008) were significantly associated. Among the migraine patients, the vast majority, 34/42 (80.95%), were classified as having severe disability.ConclusionThere is a high prevalence of migraine in patients with fibromyalgia that has an associated impact on patients' lives, which makes clinical and psychosocial management of these patients necessary.